1999
DOI: 10.1021/ed076p592
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy: The Sensitization of Cancer Cells to Light

Abstract: Photodynamic therapy, a promising, new approach for destroying malignant cells, takes advantage of light, oxygen, and a drug (photosensitizer) that preferentially localizes in rapidly growing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 4 publications
2
23
0
1
Order By: Relevance
“…Photodynamic therapy (PDT) is a rapidly expanding therapeutic modality for the treatment of a number of diseases including cancer [ 1 - 3 ]. PDT employs a photosensitizer which, upon irradiation, produces singlet oxygen ( 1 O 2 ) that damages cells [ 4 , 5 ]. One major objective of PDT is the search of new photosensitizers with high water solubility, low dark cytotoxycity, high capacity to penetrate the plasma membrane and generate 1 O 2 , and an ability to interact with specific cellular targets [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a rapidly expanding therapeutic modality for the treatment of a number of diseases including cancer [ 1 - 3 ]. PDT employs a photosensitizer which, upon irradiation, produces singlet oxygen ( 1 O 2 ) that damages cells [ 4 , 5 ]. One major objective of PDT is the search of new photosensitizers with high water solubility, low dark cytotoxycity, high capacity to penetrate the plasma membrane and generate 1 O 2 , and an ability to interact with specific cellular targets [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, it was needed to have a PS/quencher system that would uniquely produce SO by the Type II mechanism for PDT applications. 12 It has been shown that SO is the responsible species for the selective destruction of malignant tumor cells, and it has been recognized that the therapeutic efficiency of PDT may be completely reversed depending on whether Type I or Type II mechanisms are operating. 13 Thus, it is imperative to have a PS/quencher pair system in which its main photooxygenation pathway would be of the Type II mechanism, which is well known to produce SO only.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] PDT involves the systemic or topic administration of a photosensitizer which, activated by light, produces singlet oxygen and other reactive oxygen species (ROS) that cause irreversible photodamage to cancer cells. 4,5 The basic objective in PDT research is the search for new and efficient photosensitizers with desired properties such as minimum dark cytotoxycity, high capacity to generate singlet oxygen and ROS, greater retention in diseased tissues over healthy tissues, chemical stability and good cellular uptake. [6][7][8] Though a number of new phosensitisers have been proposed, [9][10][11][12][13] the one most widely used in clinic is Photofrin.…”
Section: Introductionmentioning
confidence: 99%